Leachability of metals from soil contaminated by mining activities - GÖKYAY, ORHAN (MARY ANN LIEBERT INC, 2006)
Heavy metal contamination of soil and subsequent fouling of groundwater are common problems at many metalliferous mining sites. There are various treatment processes for the cleanup of soils contaminated with heavy metals. Soil washing that involves separation of contaminants from the soil by solubilizing them in a washing solution, is one of the most frequently used techniques. In this study, applicability of soil washing technique to a contaminated soil originating from an old and smelting area in North Cyprus was investigated by conducting a series of leaching tests. A set of batch tests were conducted to optimize the reaction time and to find the most effective washing solution. Results of batch tests showed that 3-h reaction time with EDTA solution was suitable to be used in column tests. Similar trends also were found with the column tests. The results of batch and column leaching experiments conducted in this study using a naturally contaminated soil from a smelting facility indicate that copper, and to a lesser degree cadmium, can be extracted from this sample using EDTA solution. The results further suggest that when 0.1 M-500 mL EDTA is applied to the sample soil, the order of mobility of metals can be classified as follows: Cu. > Cd > Fe.
Keywords: soil washing; heavy metal leaching; EDTA; HEAVY-METALS; EDTA; REMEDIATION; EXTRACTION; RECOVERY